Scope and Features of Museum Setup Techniques in Oral Pathology - Parasakthi , M. (Journal of Biomedical and Pharmaceutical Research, 2020)
The preservation of pathological specimens has become very significant as it is a potential teaching tool and important source of data. Museum has been made compulsory in medical and dental schools by various countries as it is not a mere storage of old and rare specimens, but a vital learning aid in the field of medicine. The procedure of museum setup requires both scientific and technical skills. The term ‘Museum technology’ together constitutes the method of collection, preservation and storage of specimens. This article aims to review the basics in setting up a museum. Emerging advancements in museum techniques are also highlighted.